Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1111/apa.13154
|View full text |Cite
|
Sign up to set email alerts
|

Children with congenital colorectal malformations often require special education or remedial teaching, despite normal intelligence

Abstract: Despite normal intelligence, more than half of these patients received special education or remedial teaching. In addition, problems with sustained attention were found. These findings are important for long-term care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
(31 reference statements)
1
10
0
Order By: Relevance
“…The majority of patients that remained in our database until the age of 18 had a normal intelligence, but their sustained attention was below the norm. This data is consistent with Hondel's studies, which also suggest that these patients should benefit from special education or remedial teaching [29,30]. All the children from our sample were enrolled in normal schools.…”
Section: Discussionsupporting
confidence: 91%
“…The majority of patients that remained in our database until the age of 18 had a normal intelligence, but their sustained attention was below the norm. This data is consistent with Hondel's studies, which also suggest that these patients should benefit from special education or remedial teaching [29,30]. All the children from our sample were enrolled in normal schools.…”
Section: Discussionsupporting
confidence: 91%
“…Patients with HSCR have shown an increased need for special education at school when compared with controls, although when assessing intelligence no differences are apparent. 135…”
Section: Quality Of Lifementioning
confidence: 99%
“…Previous studies of children born with various congenital malformations have reported attention difficulties, such as significantly worse scores in working memory in 41% (17) and sustained attention levels that were lower than the general population (18,19). One study also found that their risk of having high-risk scores for inattention and hyperactivity were three to four times higher than the general population (20).…”
Section: Discussionmentioning
confidence: 97%